A Comparison of the Number of Lymph Nodes Dissected in Obese Versus Normal Weight Women [11P]. (May 2016) - Filippi, Alexandra; Crnosija, Natalie; Pearl, Michael L.
Abstract : INTRODUCTION: We evaluated the association between body mass index (BMI) and number of lymph nodes obtained at pelvic lymphadenectomy (total, right-side, and left-side). We hypothesized the number of lymph nodes removed during pelvic lymphadenectomy does not vary based on BMI. METHODS: This study was IRB approved. We retrospectively reviewed the medical records of all patients undergoing surgical staging with planned pelvic lymphadenopathy via laparotomy for gynecologic malignancies. We performed Wilcoxon rank-sum, Kruskal-Wallis and Dunn's tests to compare the median nodal count based on categorized BMI (normal, obese, morbidly obese). Using negative binomial regression, we modeled associations between independent variables and the number of pelvic nodes (total, right-sided, left-sided). RESULTS: The median number of total, right-side and left-side lymph nodes dissected from obese patients were significantly lower compared to normal weight patients. The median number of total nodes and left-sided nodes was significantly lower in morbidly obese patients compared to normal weight patients. The median number of nodes dissected in obese patients did not differ from morbidly obese. The expected log count of dissected total nodes among obese women was 0.11 lower compared to normal weight women, with covariates controlled. This relationship is echoed in right-side, but not left-side node regressions. CONCLUSION: The obesity epidemic is a relevant concern in gynecologic oncology, as surgery remains a mainstay of treatment. Body habitus presents a technical challenge to surgeons with potential implications for management decisions such as adjuvant therapy. We intend to further investigate if these results hold true with robotic surgery.